2012
DOI: 10.18632/oncotarget.707
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Chemical Screens Identify Disulfiram as an Inhibitor of Human Glioblastoma Stem Cells

Abstract: Glioblastoma Multiforme (GBM) continues to have a poor patient prognosis despite optimal standard of care. Glioma stem cells (GSCs) have been implicated as the presumed cause of tumor recurrence and resistance to therapy. With this in mind, we screened a diverse chemical library of 2,000 compounds to identify therapeutic agents that inhibit GSC proliferation and therefore have the potential to extend patient survival. High-throughput screens (HTS) identified 78 compounds that repeatedly inhibited cellular prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 62 publications
(80 reference statements)
6
112
1
Order By: Relevance
“…Thus, the independent validation of activity against the patient-derived glioma cells, DSF's low nanomolar efficacy on these cells, BBB penetration, and its extensive multi-decade clinical use with very little evidence of adverse drug reactions made it desirable to pursue in a rigorous preclinical assessment regime. DSF requires copper for effective killing and inhibition of self-renewal of genetically distinct patient-derived BTICs As described above, DSF was found to be highly effective at killing a wide range of patient-derived BTICs, an observation consistent with recent in vitro reports using human glioma cell lines (17,18,41,43); however, in vivo testing has not been performed and discrepancies with respect to the IC 50 and the requirement of copper for its therapeutic effects exist (17,18). We found that while some patient-derived BTICs were sensitive to the treatment with DSF alone (Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, the independent validation of activity against the patient-derived glioma cells, DSF's low nanomolar efficacy on these cells, BBB penetration, and its extensive multi-decade clinical use with very little evidence of adverse drug reactions made it desirable to pursue in a rigorous preclinical assessment regime. DSF requires copper for effective killing and inhibition of self-renewal of genetically distinct patient-derived BTICs As described above, DSF was found to be highly effective at killing a wide range of patient-derived BTICs, an observation consistent with recent in vitro reports using human glioma cell lines (17,18,41,43); however, in vivo testing has not been performed and discrepancies with respect to the IC 50 and the requirement of copper for its therapeutic effects exist (17,18). We found that while some patient-derived BTICs were sensitive to the treatment with DSF alone (Fig.…”
Section: Resultssupporting
confidence: 84%
“…We therefore focused upon further assessment of disulfiram. While the evaluation of DSF is certainly not unique in the cancer setting (14-16, 19, 25, 27, 40), including studies in glioma (17,41,42), in vivo preclinical assessment for glioblastoma has not been performed. Thus, the independent validation of activity against the patient-derived glioma cells, DSF's low nanomolar efficacy on these cells, BBB penetration, and its extensive multi-decade clinical use with very little evidence of adverse drug reactions made it desirable to pursue in a rigorous preclinical assessment regime.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we identified 13 drugs that were effective as single agents. Some of them were previously suggested as therapeutic candidates for GBM as single agents such as Doxorubicin hydrochloride, 21 Camptothecine (S,C), 22 Proscillaridin A, 15 Pyrivinium pamoate, 23 and Niclosamide. 24 We report Alexidine dihydrochloride, Monensin sodium salt, Lanatoside C, Digitoxigenin, Digoxigenin, Digoxin, Quinacrine dihydrochloride, Terfenadine and Astemizole as novel drugs that can be therapeutic candidates for GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the discovery of a CSC-targeting drug would significantly improve chemotherapy outcomes for NSCLC patients. The antialcoholism drug disulfiram (DSF) has been shown to have an anticancer effect against prostate cancer, breast cancer, brain tumours, leukaemia, cervical adenocarcinoma and NSCLC [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Furthermore, DSF has been shown to be an irreversible aldehyde dehydrogenase (ALDH) inhibitor targeting CSCs [22,[35][36].…”
Section: Introductionmentioning
confidence: 99%